Comparison of McKeown Minimally Invasive Esophagectomy vs sweet esophagectomy for esophageal squamous cell carcinoma: A retrospective study - Yu, Fan; Zhang, Yaozhong; Xu, Haidi; Li, Kuankuan; Gheng, Jingge; Lin, Chenxi; Li, Lei; Wang, Na; Wang, Lei (Frontiers in Oncology, 2022)
There are two most widely used transthoracic esophagectomy methods: the McKeown Minimally Invasive esophagectomy (McKeown MIE) and the Sweet Esophagectomy. We evaluated and compared the therapeutic effects of these two methods to determine the appropriate method for the treatment of middle and lower third esophageal cancer patients who received neoadjuvant chemotherapy combined with immunotherapy (NACI). We retrospectively analyzed 43 sweet esophagectomy cases received NACI and 167 cases with McKeown MIE in the fourth hospital of Hebei Medical University from December 2019 to May 2022. This retrospective observational study showed that Sweet esophagectomy and McKeown MIE after NACI therapy for resectable ESCC patients appeared to be safe with low operative mortality and morbidity rate in the current population. In addition, sweet esophagectomy was associated with a lower incidence of severe complications and shorter hospital stay for patients over 70 years of age compared with McKeown MIE. There were no differences were found in length of stay, mortality and complication incidence rate between the two groups. The Sweet approach has advantage in hospital stay for the treatment of the elderly NACI patients with middle or lower third esophageal squamous cell carcinoma. In conclusion, Sweet esophagectomy and McKeown MIE are both safe, effective, and worthwhile approaches for ESCC patients in immunotherapy age.